2022
DOI: 10.1111/ppl.13762
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the water stress index concept: Thermographic assessment of Arabidopsis transpiration

Abstract: Water stress may greatly limit plant functionality and growth. Stomatal closure and consequently reduced transpiration are considered as early and sensitive plant responses to drought and salinity stress. An important consequence of stomatal closure under water stress is the rise of leaf temperature (Tleaf), yet Tleaf is not only fluctuating with stomatal closure. It is regulated by several plant parameters and environmental factors. Thermal imaging and different stress indices, incorporating actual leaf/crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…This minimises the effect of variability derived from factors such as variations in air vapour pressure deficit, differences in plant leaf surfaces or even changes in the orientation of the sampled leaves (Maes & Steppe, 2012; Costa et al, 2013). It is, therefore, appropriate to use plants cultivated in growth chambers with controlled environmental variables (Savvides et al, 2022). In our study, infrared thermal images showed clear changes in leaf temperature (Figure 2A) and, therefore, in inferred transpiration during graft healing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This minimises the effect of variability derived from factors such as variations in air vapour pressure deficit, differences in plant leaf surfaces or even changes in the orientation of the sampled leaves (Maes & Steppe, 2012; Costa et al, 2013). It is, therefore, appropriate to use plants cultivated in growth chambers with controlled environmental variables (Savvides et al, 2022). In our study, infrared thermal images showed clear changes in leaf temperature (Figure 2A) and, therefore, in inferred transpiration during graft healing.…”
Section: Resultsmentioning
confidence: 99%
“…Scale‐up of the technique presented here has high potential to improve the yield of grafted tomato (and analogous crops). However, to achieve this, several recommendations should be taken into account: to be effective, thermography for monitoring transpiration requires that the environmental conditions should be controlled to the greatest extent possible, trying to take the measurements at the same hour of the day and avoiding the effect of wind or variations in light or humidity (Poirier‐Pocovi & Bailey, 2020; Savvides et al, 2022). If applying this method to plants grown in a greenhouse, then thermography should be used in sunny conditions and on plants in well‐watered substrates (Poirier‐Pocovi & Bailey, 2020; Vialet‐Chabrand & Lawson, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From an ECw of 2.6 dS m -1 for combination C1 and 1.6 dS m -1 for C3, there was a reduction in transpiration (Figure 3A), i.e., activating a plant defense mechanism associated with stomatal closure (Figure 2A). Transpiration is a process in which energy in the form of latent heat is transferred from the leaf to the air, being a mechanism of acclimatization of the plant to stress (Savvides et al, 2022). Pinheiro et al (2022) mention that there is a close relationship between gs and E because the flow of water vapor to the atmosphere decreases when the stomata are closed, thus triggering a process of reduction in transpiration due to the decrease in stomatal conductance.…”
Section: Resultsmentioning
confidence: 99%